Endoscopic Removal of Ingested Dentures and Dental Instruments: A Retrospective Analysis - Ken-ichi Mizuno; Kazuya Takahashi; Kentaro Tominaga; Yuki Nishigaki; Hiroki Sato; Satoshi Ikarashi; Kazunao Hayashi; Takashi Yamamoto; Yutaka Honda; Satoru Hashimoto; Kenya Kamimura; Manabu Takeuchi; et al. (Gastroenterology Research and Practice)
Background. Dentures and dental instruments are frequently encountered ingested foreign bodies. The aim of the present study was to assess the safety and efficacy of endoscopically removing ingested dental objects. Methods. Twenty-nine consecutive patients with 29 dental objects who were treated at the Niigata University Medical and Dental Hospital from August 2009 to December 2015 were retrospectively reviewed. Characteristics of the patients and the ingested dental objects, the clinical features and findings of radiological imaging tests, and outcomes of endoscopic removal were analyzed. Results. Patients’ mean age was 62.9±21.0 years. The ingested dental objects included 23 dentures (13 crowns, 4 bridges, 4 partial dentures, and 2 other dentures) and 6 dental instruments. Twenty-seven upper gastrointestinal endoscopies and 2 colonoscopies were performed, and their success rates were 92.6% and 100%, respectively. There were 2 cases of removal failure; one case involved an impacted partial denture in the cervical esophagus, and this case required surgical removal. Conclusions. Endoscopic removal of ingested dentures and dental instruments is associated with a favorable success rate and acceptable complications. The immediate intervention and appropriate selection of devices are essential for managing ingested dental objects.